Doppler ultrasound in the assessment of severity of coarctation of the aorta and interruption of the aortic arch. Issue 1 (January 1987) - Houston, A B; Simpson, I A; Pollock, J C; Jamieson, M P; Doig, W B; Coleman, E N
Abstract : Doppler ultrasound was used to investigate 48 infants and children (age 2 days-16 years, weight 1.0-58 kg) with aortic arch abnormalities. In only 38 of the 42 with an important coarctation was an increased blood flow velocity from the distal arch demonstrated. In three with interruption of the aortic arch an increased velocity recorded from the region of the distal arch was thought to represent ductal flow. There was little difference between the peak to peak and instantaneous maximum gradients in the 20 patients with important coarctation in whom direct pressure measurements both proximal and distal to the obstruction were made at catheterisation. There were poor agreements between Doppler and measured peak to peak and instantaneous gradients in the 17 patients found to have both an increased velocity and important coarctation. It is concluded that although an increased blood flow velocity in the distal arch is usually demonstrated in coarctation this may not occur with severe obstruction. Furthermore, the maximum velocity is not related to the anatomical severity of the obstruction and the Doppler estimate of pressure drop in coarctation may not even reliably predict that measured at catheterisation.